Corporate accountability in Southeast Asia: National action plans for responsible business conduct under International Law - MOHAN, Mahdev (Institutional Knowledge at Singapore Management University, 2015)
Beyond transnational litigation which seeks to hold corporations accountable for their misconduct overseas through judicial recourse, the risk of human rights abuses should be mitigated by embedding good practices locally through domestic laws and policies. The United Nations proposed Guiding Principles for transnational and other businesses for this purpose in 2011. It has been suggested that National Actions Plans should give effect, or at the very least policy coherence, to the international standards enshrined in the Guiding Principles. This article argues that, properly devised, such plans are invaluable, and can help to reinforce regional imperatives under international law. In Southeast Asia, particularly, the prospect of corporate accountability should be measured by existing or emergent regulatory norms in ASEAN, a regional bloc that aims to achieve parity of rules and regulations across the ten countries through economic integration.